2014
DOI: 10.1016/s0254-6272(14)60095-9
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharides from Tricholoma matsutake and Lentinus edodes enhance 5-fluorouracil-mediated H22 cell growth inhibition

Abstract: Polysaccharides from Lentinus edodes and Tricholoma matsutake could enhance the efficacy of 5-FU-mediated H22 cell growth inhibition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 19 publications
0
14
0
2
Order By: Relevance
“…reported a maintained or decreased granulocytes/lymphocytes ratio during follow‐up and supposed lentinan may increase the cellular response. Findings from latest basic cell and animal researches of lentinan in vitro and in vivo primary elucidated direct anticancer effects and immune modifying effects: (1) lentinan alone inhibits cancer cell proliferation and induce cell apoptosis ; (2) a combination of lentinan with chemotherapy drugs or monoclonal antibodies enhances their toxicity to cancer cell ; (3) lentinan can be blinding to activate macrophages and other monocytes . Anticancer effects were found to be mainly p53‐dependent, and involved MAPK signaling pathways activation and reactive oxygen species overproduction ; and immune modifying effects of lentinan mainly because of its activation of macrophages and monocytes though binding to specific receptors on the cells, and further induction of cytokine release, complement activation, and antibody‐dependent cell‐mediated cytotoxicity .…”
Section: Discussionmentioning
confidence: 99%
“…reported a maintained or decreased granulocytes/lymphocytes ratio during follow‐up and supposed lentinan may increase the cellular response. Findings from latest basic cell and animal researches of lentinan in vitro and in vivo primary elucidated direct anticancer effects and immune modifying effects: (1) lentinan alone inhibits cancer cell proliferation and induce cell apoptosis ; (2) a combination of lentinan with chemotherapy drugs or monoclonal antibodies enhances their toxicity to cancer cell ; (3) lentinan can be blinding to activate macrophages and other monocytes . Anticancer effects were found to be mainly p53‐dependent, and involved MAPK signaling pathways activation and reactive oxygen species overproduction ; and immune modifying effects of lentinan mainly because of its activation of macrophages and monocytes though binding to specific receptors on the cells, and further induction of cytokine release, complement activation, and antibody‐dependent cell‐mediated cytotoxicity .…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis was confirmed by the rapid stimulation of the production of reactive oxygen species, a loss of mitochondrial membrane potential, and an increase in intracellular Ca 2+ levels [7]. Mouse models have shown that polysaccharides derived from LE inhibit tumor growth and 5-FU production [8]. Furthermore, serum levels of TNFalpha, IL-2, and IFN-gamma, frequencies of CD4 + and CD8 + T cells in the spleen, and splenic NK and CTL activities were significantly increased in these mouse models [8].…”
mentioning
confidence: 99%
“…Mouse models have shown that polysaccharides derived from LE inhibit tumor growth and 5-FU production [8]. Furthermore, serum levels of TNFalpha, IL-2, and IFN-gamma, frequencies of CD4 + and CD8 + T cells in the spleen, and splenic NK and CTL activities were significantly increased in these mouse models [8]. These effects of polysaccharides derived from LE may also be involved in the pathophysiology of shiitake dermatitis.…”
mentioning
confidence: 99%
“…In Mausmodellen inhibieren LE-Polysaccharide nachweislich das Tumorwachstum und die 5-FU-Produktion [8]. Darüber hinaus stiegen in diesen Mausmodellen die Serumspiegel von TNF-alpha, Il-2 und IFN-gamma, die Anzahl von CD4+ und CD8+ T-Zellen in der Milz und die Aktivitäten von NK-und CTL-Zellen deutlich an [8]. Diese Effekte der LE-Polysaccharide könnten auch bei der Pathophysiologie der Shiitake-Dermatitis eine Rolle spielen.…”
unclassified